(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
In PTKs, the pneumatic method is used to transport seeded cotton between departments. SS-15A separators are used to separate the seeded cotton from the air stream coming through the pneumatic conveyor. Improving the performance of the SS-15A separator by improving the vacuum valve